2010
DOI: 10.1248/jhs.56.296
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Repeated Treatment with Hericium erinaceum in Mice Subjected to Middle Cerebral Artery Occlusion

Abstract: The neuroprotective effects of Hericium erinaceum (H. erinaceum) were studied in mice subjected to middle cerebral artery (MCA) occlusion. Infarct volumes were markedly reduced in mice receiving 14 days of H. erinaceum (300 mg/kg) treatment prior to 4-hr MCA occlusion. Moreover, 14-day pre-ischemic H. erinaceum treatment significantly increased the levels of nerve growth factor (NGF) in both the cortex and striatum of mice subjected to 4-hr MCA occlusion. However, pre-ischemic H. erinaceum treatment had no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
(38 reference statements)
0
14
0
1
Order By: Relevance
“…Previous studies showed that H. erinaceus oral supplementation in mice with learning and memory deficits induced by intracerebroventricular administration of A β (25–35) amyloid β (25–35) peptide prevented cognitive deficits in a memory recognition task but not in a spatial working task [3]. Based on these findings, we decided to test the effect of H. erinaceus on recognition memory in wild-type mice by using the NOR task (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that H. erinaceus oral supplementation in mice with learning and memory deficits induced by intracerebroventricular administration of A β (25–35) amyloid β (25–35) peptide prevented cognitive deficits in a memory recognition task but not in a spatial working task [3]. Based on these findings, we decided to test the effect of H. erinaceus on recognition memory in wild-type mice by using the NOR task (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Hazekawa et al [3] described the neuroprotective effects of H. erinaceus dietary supplementation in mice subjected to middle cerebral artery occlusion. Furthermore, scores on the cognitive function scale improved after oral administration of H. erinaceus in patients suffering from mild cognitive impairment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Existing data have suggested that there is a neuroprotective effect of dietary supplementation with H. erinaceus in mice subjected to middle cerebral artery occlusion [23]. Furthermore, H. erinaceus provided a partial recovery of intellectual function of patients with a mild cognitive impairment or against other forms of neurodegenerative diseases, including dementia and Alzheimer’s [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…В экспериментальной модели инсульта показано, что введение эриноцина А в первые 90 минут после развития острого нарушения мозгового кровообращения приводило к ослаблению экспрессии провоспалительных цитокинов, снижению проявлений апоптоза и уменьшению объема инфаркта мозга [106]. Предварительный прием в течение 14 дней экстракта Hericium erinaceus до развития инсульта, смоделированного путем контролируемой окклюзии средней мозговой артерии, способствовал достоверному возрастанию синтеза NGF и регрессу неврологических симптомов [107].…”
Section: ключевые слова: постинсультные когнитивные нарушения; нейропunclassified